Spanish Relief Committee - Knitted garments for Spain : inter-departmental correspondence - Tewson, Vincent
028-0107-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From: H. V. Tewson. To: Sir Walter Citrine. Department: Secretary's. Date: 12th January, 1937. SUBJECT. SPANISH RELIEF COMMITTEE - KNITTED GARMENTS FOR SPAIN. I have had a talk with Miss Sutherland in regard to what is being done and I find they have five centres actually organised. I put it to her as to whether it would not be of assistance to their Committee if the grant were made on a basis of so much for each centre open. This would have the effect of putting the organisers on their metal by making them realise that the more centres they could organise the greater would be the amount of money forthcoming. Miss Sutherland thinks that a very good idea. I understand that the Southampton centre has taken about £8 worth of wool which will last them a little over a month. What do you think of the suggestion that we should give them an initial grant of £50, i.e. £10 per centre in respect of each one which is already formed and a further £10 for each centre they are able to organise? 292/946/28/107